Hot diffuse emission in the nuclear starburst region of NGC 2903 - Yukita, M.; Swartz, D.; Tennant, A.; Soria, Roberto; Irwin, J. (Institute of Physics Publishing, Inc., 2012)
We present a deep Chandra observation of the central regions of the late-type barred spiral galaxy NGC 2903. The Chandra data reveal soft (kTe ~ 0.2-0.5 keV) diffuse emission in the nuclear starburst region and extending ~2' (~5 kpc) to the north and west of the nucleus. Much of this soft hot gas is likely to be from local active star-forming regions; however, besides the nuclear region, the morphology of hot gas does not strongly correlate with the bar or other known sites of active star formation. The central ~650 pc radius starburst zone exhibits much higher surface brightness diffuse emission than the surrounding regions and a harder spectral component in addition to a soft component similar to the surrounding zones. We interpret the hard component as also being of thermal origin with kTe ~ 3.6 keV and to be directly associated with a wind fluid produced by supernovae and massive star winds similar to the hard diffuse emission seen in the starburst galaxy M82. The inferred terminal velocity for this hard component, ~1100 km s–1, exceeds the local galaxy escape velocity suggesting a potential outflow into the halo and possibly escape from the galaxy gravitational potential. Morphologically, the softer extended emission from nearby regions does not display an obvious outflow geometry.However, the column density through which the X-rays are transmitted is lower in the zone to the west of the nucleus compared to that from the east and the surface brightness is relatively higher suggesting some of the soft hot gas originates from above the disk: viewed directly from the western zone but through the intervening disk of the host galaxy along sight lines from the eastern zone. There are several point-like sources embedded in the strong diffuse nuclear emission zone. Their X-ray spectra show them to likely be compact binaries. None of these detected point sources are coincident with the mass center of the galaxy and we place an upper limit luminosity from any point-like nuclear source to be <2 × 1038 erg s–1 in the 0.5-8.0 keV band, which indicates that NGC 2903 lacks an active galactic nucleus. Heating from the nuclear starburst and a galactic wind may be responsible for preventing cold gas from accreting onto the galactic center.